2022
DOI: 10.3390/cancers14205099
|View full text |Cite
|
Sign up to set email alerts
|

Compound C Inhibits Ovarian Cancer Progression via PI3K-AKT-mTOR-NFκB Pathway

Abstract: Epithelial Ovarian cancer (OvCa) is the leading cause of death from gynecologic malignancies in the United States, with most patients diagnosed at late stages. High-grade serous cancer (HGSC) is the most common and lethal subtype. Despite aggressive surgical debulking and chemotherapy, recurrence of chemo-resistant disease occurs in ~80% of patients. Thus, developing therapeutics that not only targets OvCa cell survival, but also target their interactions within their unique peritoneal tumor microenvironment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Considerable drawbacks involved in "chemotherapy treatment" are the serious toxicity and drug resistance. Numerous studies have affirmed that natural compounds with chemo preventive property could improve the ovarian cancer response rate in combination with chemotherapeutic agents both in vitro and in vivo [26][27][28][29] . Though Wedelolactone presents limited bioavailability, low doses of physiologically practicable concentrations are appropriate for its chemotherapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable drawbacks involved in "chemotherapy treatment" are the serious toxicity and drug resistance. Numerous studies have affirmed that natural compounds with chemo preventive property could improve the ovarian cancer response rate in combination with chemotherapeutic agents both in vitro and in vivo [26][27][28][29] . Though Wedelolactone presents limited bioavailability, low doses of physiologically practicable concentrations are appropriate for its chemotherapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK is activated by phosphorylation of AMPK-α subunit at threonine-172 in response to growth factors (GF) through Ca 2+ /calmodulin-dependent protein kinase kinase β (CaMKKβ) and is essential for GF-mediated AKT activation and biological functions [ 36 , 37 , 38 ]. Previously, we and others have reported that compound C, an AMPK inhibitor, inhibits the activation of AKT indicating that AMPK is an important regulator of AKT pathway [ 17 , 39 ]. Moreover, AKT is also activated by direct activation of epidermal growth factor receptor (EGFr) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 Compound C passed PI3K/AKT/mTOR/NF- κB pathway has been shown to inhibit OC progression. 15 Furthermore, CXCR4 has been shown to modulate PI3K/Akt/mTOR signaling in epithelial OC (EOC). In addition, the CXCR4-PI3K/Akt/mTOR axis promotes the formation of cancer stem cells (CSCs) and epithelial-mesenchymal transition (EMT), resulting in resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Inhibitors of the PI3K/AKT/mTOR pathway have been shown to dramatically slow the growth of OC. 15 In roughly 70% of OC cases the PI3K/AKT/mTOR pathway is upregulated, which results in increased angiogenesis, cell survival, and metabolism. 16 Several clinical studies have shown that the PI3K pathway is a promising target for the treatment of OC.…”
Section: Introductionmentioning
confidence: 99%